A Multirobot System for Distributed Area Coverage and Signal Searching in Large Outdoor Scenarios*. Issue 8 (19th November 2015) - Garzón, Mario; Valente, João; Roldán, Juan Jesús; Cancar, Leandro; Barrientos, Antonio; Del Cerro, Jaime
Abstract : This work presents a complete multirobot solution for signal searching tasks in large outdoor scenarios. An evaluation of two different coverage path‐planning strategies according to field size and shape is presented. A signal location system developed to simulate mines or chemical source detections is also described. The solution presented is a pioneer in evaluating multimaster robotics operative system architectures with a fleet of robots in real scenarios. This solution minimizes the use of communications bandwidth required for full operation. Finally, field results are provided, and the advantages of the implemented solution are analyzed.